2012
DOI: 10.1161/circinterventions.112.972182
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity C-Reactive Protein and Outcomes Following Percutaneous Coronary Intervention in Contemporary Practice

Abstract: Background-High sensitivity C-reactive protein (hsCRP) has been identified as a predictor of adverse cardiovascular outcomes. Whether hsCRP is a useful biomarker for risk stratification in contemporary percutaneous coronary intervention remains unknown. Methods and Results-We conducted a prospective study among 513 patients undergoing non-emergency percutaneous coronary intervention and examined the relationship between pre-and postprocedural hsCRP levels and outcomes. The patients were divided according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
(54 reference statements)
7
12
1
Order By: Relevance
“…Saadeddin et al 17 reported that, pre-procedural hsCRP elevation in 41.0% of patients with stable angina and who underwent PCI, and this was associated with a 2.27 fold higher risk of developing periprocedural myocardial injury. Herrmann et al 27 and Rhee et al 28 also described similar result in their studies. Ten percent of Group I and 4.0% of Group II had periprocedural myocardial injury in which CK-MB level was raised but less than five times of upper reference limit, or rise of CK-MB >5 times of upper reference limit without chest pain, ECG, echocardiographic changes.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Saadeddin et al 17 reported that, pre-procedural hsCRP elevation in 41.0% of patients with stable angina and who underwent PCI, and this was associated with a 2.27 fold higher risk of developing periprocedural myocardial injury. Herrmann et al 27 and Rhee et al 28 also described similar result in their studies. Ten percent of Group I and 4.0% of Group II had periprocedural myocardial injury in which CK-MB level was raised but less than five times of upper reference limit, or rise of CK-MB >5 times of upper reference limit without chest pain, ECG, echocardiographic changes.…”
Section: Discussionsupporting
confidence: 71%
“…27 In that study, atherosclerotic burden and disease activity that determine longterm clinical outcomes after PCI rather than inflammation per se. But Preprocedural hsCRP level seems to be a marker of baseline risk and is independently associated with the risk of periprocedural MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the circulating level of CRP, considered currently considered to represent a "golden marker for inflammation", reflects the severity of inflammatory response and plays a significant role in the development of atherosclerosis, many studies have attempted to predict the future cardiovascular events and the response to therapy based on CRP-based risk classification (14,15). It has been proved that high levels of circulating CRP upon admission correlates with the extent of the infarction, the development of postinfarction heart failure and the presence of severe lesion by angiography, while in patients undergoing primary PCI, high CRP level before the procedure predicted the rate of early complications (16,17). In a previous study of Pietila et al, high serum C-reactive protein concentrations in acute myocardial infarction patients were found to predict an increased mortality up to 6 months following the infarction (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that statins to treat high cholesterol could reduce the incidence of cardiovascular events after PCI . In previous studies, we demonstrated that Xuezhikang (an extract of Chinese red yeast rice whose main ingredient is lovastatin), especially large‐dose Xuezhikang, decreased serum levels of hs‐CRP, matrix metallopeptidase 9, and low‐density lipoprotein cholestero .…”
Section: Introductionmentioning
confidence: 85%